Le rôle des séries télévisées turques dans la circulation des modèles urbains et des modes d’habiter en Iran - Mina Saïdi-Sharouz (EchoGéo)
In this article, we examine the role of the very successful Turkish series, no allowed in Iran but broadcast by satellite (such as The Magnificent Century, Forbidden Love and Bargrizan) in the transfer of urban models and ways of living in Iran. How the Turkish series contribute first to the development of tourism, then to the informal importation of the prêt-à-porter and finally to the opening of the Iranian market on the products of furniture and architecture, real economic pole which transforms the modes to live and acts gradually on the spaces of Iranian cities.